Surface Water Quality : Have the Laws Been Successful? - Patrick, Ruth (Book collections on Project MUSE., 2014)
Addressing ecologists, legislators, lawyers, and industrialists alike, Ruth Patrick asks what has been accomplished with the millions of dollars spent on upgrading our surface waters. Has the water improved in spite of the fact that the crayfish, snails, and algae are not those that one would expect to find in natural rivers and estuaries? To evaluate the success of environmental laws over the past two decades, the author examines the aquatic life of river systems in the Delaware Valley, Texas, and Georgia--the only areas in the United States where she found enough biological data to determ.